Membangun RT/RW Net Dengan Titik Pointing Antar Wilayah - Adam Laxmana Mufti; Azmuri Wahyu Azinar; Hindarto Hindarto; Yunianita Rahmawati (LPPM UBHINUS MALANG, 2025)
The digital divide between urban and rural areas in Indonesia remains a significant challenge in the current digital era, with limited internet access in remote regions hindering economic, educational, and social progress. This research aims to develop a wireless LAN-based RT/RW Net system as a solution to enhance efficient and affordable internet access. The system utilizes point-to-point access between regions using specialized routers to overcome geographical and physical barriers, thereby enabling internet access in hard-to-reach areas. By leveraging WiFi 5 technology as a solution for better range and performance, along with ease of operation and affordable construction costs, the system is designed for efficiency. Device configuration is carried out using the built-in application of the TP-Link EAP 110 router, facilitating easier and more efficient management. The PPDIOO (Prepare, Plan, Design, Implement, Operate, Optimize) research methodology is chosen as the approach for developing the RT/RW Net network. The advantages of this method include structured and systematic design capabilities, greater flexibility in meeting design needs, and the ability to optimize the quality of the network once it is operational. This method can also analyze and build networks according to local geographical conditions. Expected outcomes include improved quality and reliability of the RT/RW Net network, provision of cheaper and more convenient internet access for communities, and contributions to a more equitable dissemination of information and communication technology across Indonesia, enabling communities to enjoy better access to information, broader educational opportunities, and enhanced economic prospects.